BubR1 kinase: protection against aneuploidy and premature aging. Issue 6 (June 2015) - Kapanidou, Maria; Lee, Semin; Bolanos-Garcia, Victor M.
Highlights BubR1 exhibits multiple roles in the mitotic checkpoint and beyond. BubR1 complexes: new pharmacological targets for anticancer therapy? BubR1 contributes to preventing premature aging.